(untitled) (Docentes 2.0 Journal, 2021)
Based on the fundamental role of the teacher in education and considering that it is said that teachers teach solutions, it falls into a wrong belief. This COVID-19 pandemic has revealed such a marked digital divide existing in educational environments and the need for the implementation of innovative learning strategies, mediated by basic but functional technological tools, that allow mediation between knowledge and its actors. The objective of this proposed research was to analyze, based on the use of technologies in learning environments. The categories that consider the dynamic role in teaching and turn a reflective practice-oriented to the digital competencies of the level Elementary School of the IE Telepalmeritas, Municipality of San Luis de Gaceno, Department of Boyacá. In this case, for the development of the study, the qualitative research methodology is used, with a descriptive approach, based on the semi-structured interview protocol. It then found that it should be committed to meaningful learning based on experiences and interactions with digital tools from teachers to be multiplied in the classroom, promoting autonomous learning through responsible digital practices.